When Do Gender-Diverse Teams Engage More Investors? Evidence of Threshold Alignment Benefits at Techstars - Kanze, Dana; Piazza, Alessandro (Organization Science, 2026)
Through an observational field study involving quantitative and qualitative components, we explore the role of gender diversity in shaping the effectiveness of mentorship for founder teams seeking investors. Data on 984 teams of founders assigned to teams of mentors at Techstars-run accelerator programs around the world demonstrate the interteam benefits of aligned gender diversity thresholds: Founder teams characterized by the presence (absence) of gender diversity engage more investors when matched with mentor teams also characterized by the presence (absence) of gender diversity. Neither the presence of gender diversity in the founder team nor the presence of gender diversity in the mentor team exerts a positive influence on investor counts as a standalone factor, but the aligned presence of intrateam gender diversity helps ventures maximize participating investors. We find that the number of participating investors has a positive downstream impact, increasing the amount of funding that the venture raises. Results are robust to the inclusion of controls for venture, founder, and mentor characteristics, with clustering at the Techstars cohort level. Qualitative insights from 20 semistructured interviews reveal how interteam gender alignment facilitates interpersonal attraction, whereas intrateam gender diversity enables resource acquisition. We discuss the theoretical and practical implications of this phenomenon for internal-external team interactions in venture funding and beyond. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2025.20141 .